Adapting evidence-based behavioral weight loss programs for emerging adults: A pilot randomized controlled trial. (June 2019) - LaRose, Jessica Gokee; Tate, Deborah F; Lanoye, Autumn; Fava, Joseph L; Jelalian, Elissa; Blumenthal, Megan; Caccavale, Laura J; Wing, Rena R
Emerging adults are at high risk of obesity but behavioral weight loss programs do not meet their needs. Emerging adults ( N = 52, age = 22.3 ± 2 years, body mass index = 34.2 ± 5.5 kg/m 2, 46.2% non-Hispanic White) were randomly assigned to one of three behavioral weight loss programs adapted based on formative work: face-to-face behavioral weight loss, web-based behavioral weight loss, or web plus optional community sessions (Hybrid). Assessments occurred at 0 and 3 months. Engagement and self-monitoring were highest in Hybrid. Intent-to-treat weight losses were −2.8 ± 2.9 percent in face-to-face behavioral weight loss, −2.2 ± 4.5 percent in web-based behavioral weight loss, and 4.8 ± 4.9 percent in Hybrid. Percent achieving ⩾5 percent weight loss was highest in Hybrid (63%). Findings suggest potential for adapted behavioral weight loss to promote engagement and weight loss in emerging adults.